Child Development Accounts and Saving for College: Mediated by Parental Educational Expectations?*. (9th February 2018) - Kim, Youngmi; Huang, Jin; Sherraden, Michael; Clancy, Margaret
Abstract : Objective: Child Development Accounts (CDAs) are universal and progressive savings accounts that facilitate saving for long‐term developmental goals, including postsecondary education. We examine whether parents' educational expectations for their children motivate them to increase saving for children's education and whether parents' expectations mediate the positive effect of CDAs on parental saving. Methods: We use logistic regressions to analyze data from SEED for Oklahoma Kids (SEED OK), a randomized policy experiment implemented in Oklahoma ( N = 2, 161). Results: Our study shows that the likelihood of holding a 529 college savings account is greater among treatment mothers than among control‐group counterparts and greater for mothers with higher expectations. Yet, we find no evidence that parents' expectations play a mediating role in the SEED OK intervention's relationship with 529 account holding. Conclusions: Institutional supports from CDAs and enabling parents to maintain positive parental expectations would make substantial differences in parents' financial investment for their child's education.